A comparative study on initial growth and nodulation potential of sevel multipurpose tree species grown in Chittagong, Bangladesh - Hossain, M.S.; Koirala, B.; Hossain, M.K. (Banko Janakari, 2017)
Abstract available on the PDF Banko Janakari Vol.11(2) 2001: 22-26